Development and validation of a questionnaire measuring factors associated with physical activity in adolescents - Farias Júnior,José Cazuza de (2011)
OBJECTIVES: to develop a questionnaire to measure factors associated with physical activity (PA) in adolescents and analyze its reliability and validity. METHODS: a total of 248 adolescents from 14 to 19 years old took part in this study. The factors associated with PA measured were: attitude, self-efficacy, social support of PA and perceived environment. Cronbach's alpha (α) and intraclass correlation coefficients (ICC) were used to test reliability, and exploratory factor analysis to evaluate validity. RESULTS: attitude was measured as a single factor (attitude: α=0.76, ICC=0.89); self-efficacy consisted of two factors: resources for PA (α=0.76, ICC=0.75) and social support and motives for engaging in PA (α=0.76, ICC=0.67); social support was measured as two factors: support for PA from friends (α=0.90, ICC=0.89) and support for PA from parents (α= 0.81, ICC=0.91); and the environment was measured as three factors: access to and attractiveness of places to engage in PA (α=0.69, ICC=0.82), security/safety when engaging in PA (α=0.73, ICC=0.67), and general infrastructure of the neighborhood (α=0.70, ICC=0.75). CONCLUSIONS: the questionnaire exhibited satisfactory validity and reliability and can be recommended for studies investigating adolescents.